Dolor, reconocimiento y diferencia: en torno al último canto de la Ilíada - Míguez Barciela, Aida (Anales del Seminario de Historia de la Filosofía, 2008)
An interpretation of the closing of the Iliad is outlined from what according to certain analyses of Hölderlin we can call the “ideal” path characteristic of the figure of Achilles. The rupture of that “ideal” through the “catastrophe” of the poem articulates a return to that “naiv” that at the end of the Iliad is linked with the imperative to assume the pain and to keep the difference between the spheres of the man and of the god, something that we clarify by means of an analysis of the Isthmian VIII of Pindar and the reading of certain fragments of Hölderlin.